BIOACTIVE POTENTIAL OF STREPTOMYCES VARIABILIS - DV-35 ISOLATED FROM THOTTADA MARINE SEDIMENTS, KANNUR, KERALA - Mandal, Sreejetha; Divya,; Sreedharan, Veena; BHASKARA RAO, KOKATI VENKATA (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study was aimed to evaluate the bioactive potential (antimicrobial and antioxidant) of marine actinobacteria isolated from Thottada marine sediment, Kannur, Kerala. Methods: The study involved isolation of marine actinobacteria from Thottada marine sediments, followed by antimicrobial and antioxidant activity of the crude extract. Finally, identification of potential isolates. Results: In this study, a total of 6 actinobacterial colonies were isolated, out of which only one isolate DV-35 showed maximum anti-microbial and anti-oxidant activity. The isolate DV-35 showed maximum inhibitory activity against Gram-negative bacterial pathogens Pseudomonas aeruginosa (18 mm) followed by Salmonella typhi (17 mm) and Klebsiella sp. (13 mm) at a dose of 100 Î¼g/ml. In antifungal activity, extract showed maximum activity against Aspergillus niger (19 mm) followed Aspergillus flavus (17 mm) at a dose of 100 Î¼g/ml. Simultaneously the extract was evaluated for its antioxidant activity. The potential isolate DV-35 also showed moderately higher antioxidant activity in various screening assay, viz., 2,2-diphenyl-1- picrylhydrazyl scavenging assay (80.12%), metal chelating assay and reducing power assay (76%) at a concentration of 100 Î¼g/ml. Potential isolate DV-35 was identified as Streptomyces variabilis DV-35 using molecular 16S rRNA sequencing. Conclusion: The results obtained suggest that the extract is having bioactive metabolites that can be considered as a potential source for antimicrobial and anti-oxidant drug development. Keywords: Marine actinomycetes, Anti-microbial activity, Anti-oxidant activity, Pseudomonas aeruginosa, Aspergillus niger, Streptomyces variabilis.